Toward Highly Sensitive and Energy Efficient Ammonia Gas Detection with Modified Single-Walled Carbon Nanotubes at Room Temperature - Panes-Ruiz, Luis Antonio; Shaygan, Mehrdad; Fu, Yangxi; Liu, Ye; Khavrus, Vyacheslav; Oswald, Steffen; Gemming, Thomas; Baraban, Larysa; Bezugly, Viktor; Cuniberti, Gianaurelio (Giovanni) (ACS Sensors, 2018)
Fabrication and comparative analysis of the gas sensing devices based on individualized single-walled carbon nanotubes of four different types (pristine, boron doped, nitrogen doped, and semiconducting ones) for detection of low concentrations of ammonia is presented. The comparison of the detection performance of different devices, in terms of resistance change under exposure to ammonia at low concentrations combined with the detailed analysis of chemical bonding of dopant atoms to nanotube walls sheds light on the interaction of NH3 with carbon nanotubes. Furthermore, chemoresistive measurements showed that the use of semiconducting nanotubes as conducting channels leads to the highest sensitivity of devices compared to the other materials. Electrical characterization and analysis of the structure of fabricated devices showed a close relation between amount and quality of the distribution of deposited nanotubes and their sensing properties. All measurements were performed at room temperature, and the power consumption of gas sensing devices was as low as 0.6 μW. Finally, the route toward an optimal fabrication of nanotube-based sensors for the reliable, energy-efficient sub-ppm ammonia detection is proposed, which matches the pave of advent of future applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: adsorption mechanism; ammonia detection; doped carbon nanotube; gas sensor; semiconducting carbon nanotube